Advances in Integrated Soil Fertility Management in Sub-Saharan Africa: Challenges and Opportunities
DOI: 10.1007/978-1-4020-5760-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Improving cereal productivity and farmers’ income using a strategic application of fertilizers in West Africa

Abstract: In the past two years, ICRISAT, in collaboration with other International Agricultural Research Centres, National Agricultural Research and Extension Systems, has been evaluating and promoting point or hill application of fertilizer along with "Warrantage" in three West African countries, namely, Burkina Faso, Mali and Niger. The hill application of fertilizers consists of applying small doses of fertilizer in the planting hills of millet and sorghum. The combination of strategic hill application of fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0
4

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 6 publications
(4 reference statements)
8
49
0
4
Order By: Relevance
“…Cattle manure with moisture content of 15 % was used for the experiment. Mineral fertilizer application was a micro-dose of NPK at a dose of 3 g per hole (62 kg ha −1 at a sowing spacing of 80 cm × 60 cm) [19]. Varieties and cropping systems were combined to have 8 levels of treatment (M1, M2, C1, C2, M1C1, M1C2, M2C1 and M2C2).…”
Section: Methodsmentioning
confidence: 99%
“…Cattle manure with moisture content of 15 % was used for the experiment. Mineral fertilizer application was a micro-dose of NPK at a dose of 3 g per hole (62 kg ha −1 at a sowing spacing of 80 cm × 60 cm) [19]. Varieties and cropping systems were combined to have 8 levels of treatment (M1, M2, C1, C2, M1C1, M1C2, M2C1 and M2C2).…”
Section: Methodsmentioning
confidence: 99%
“…En effet, ces auteurs étaient parvenus à la conclusion que la différence entre la microdose et la dose vulgarisée n'était pas statiquement significative. De même, des études récentes ont montré des résultats similaires avec le mil sur des sols sableux du Niger (Tabo et al, 2007 ;Hayashi et al, 2008;Ibrahim et al, 2014Ibrahim et al, , 2015 ainsi qu'avec le niébé et le sorgho au Mali (Bagayoko et al, 2011) et au Burkina Faso (Taonda et al, 2008Pale et al, 2009).…”
Section: Analyses Statistiquesunclassified
“…Ces résultats sont en accord avec ceux obtenus précédemment, montrant que la microdose favorisait une augmentation du revenu des producteurs (Tabo et al, 2005(Tabo et al, , 2007Aune et al, 2007 ;Taonda et al, 2008) qui ont montré que la microdose favorisait une augmentation du revenu. Aune et al (2007) ont obtenu au Mali un RVC variant entre 9,33 et 9,37 pour le sorgho et 3,4 à 11,9 pour le mil avec des apports de 0,3 g/poquet du NPK (15-15-15) ou du DAP (18-46-0).…”
Section: Analyses Statistiquesunclassified
See 1 more Smart Citation
“…Tabo et al (2006) have shown that micro-dose (4 kg P/ha) increased millet and sorghum grain yields up to 43-120% and farmer's income were improved trough Warrantage by 52-134% in the studied countries (Burkina Faso, Mali et Niger) (Table 6.1).…”
Section: Long-term Millet Trials Phosphorus Nitrogen Crop Residue (mentioning
confidence: 88%